Development of Floor Pattern Learning Media Using 3D Interactive Software Applications for Middle School Level Arts and Culture Teachers - Fitria Khusnul (Jurnal Pendidikan Tari, 2024)
This thesis discusses problems using conventional learning media in floor pattern material is the main thing during learning. The purpose of this study to explain the process and analyze the results of the feasibility test for the development of dance learning media based on the Pyware 3D Interactive application on floor pattern material. The research method used is research and development or R&D (Research and Development) with the ADDIE development model which consists of five stages, namely analysis, design, development, implementation and evaluation. This is done by limiting it to the small-scale trial stage. Based on the results of small-scale trials from the assessment of learning experts and media experts with the result "Very Feasible". The conclusion from this study is that learning media based on the Pyware 3D Interactive application for learning dance floor patterns is “Worth” using, because it has many features that can help students and teachers optimize skills.